PENANGANAN DAN EVALUASI PROGRAM BIMBINGAN KONSELING PADA ANAK - Muhammad Fatkhan Muallifin (STPI Bina Insan Mulia Yogyakarta, 2019)
A good mentor needs to have an interest in working with other people and must have the ability to act and behave in a friendly and wise manner towards clients. In general, the teacher usually limits himself to cases that are not so severe in his class. The supervising teacher is expected to have more complete knowledge about the personality of students and techniques for conducting interviews, as well as dealing with larger cases. But even so, in very serious cases he must ask for services from experts, such as doctors, psychologists or counseling clinics that have adequate equipment. The method used is a literature review that discusses the importance of program planning and evaluation of guidance and counseling programs for children, before children carry out guidance activities, children and teachers have understood guidance programs and planning beforehand. Where the program made continues in the application process to realize certain program plans. After the application process continues to carry out the evaluation program by paying attention to evaluation techniques. So that the things that are evaluated are right on target and the results of counseling guidance are found.